Development of integrated science instructional materials using Rowntree model to promote 21st century ecoliteracy - Azmi Al Bahij; Julia Anis Handayani; Apri Utami Parta Santi; Erna Yayuk (Universitas Muhammadiyah Malang, 2025)
The 4.0 Revolution and 21st-century challenges necessitate an education system that integrates 4C skills (Critical Thinking, Communication, Collaboration, and Creativity) with environmental awareness. This study aims to develop and evaluate the feasibility, practicality, and effectiveness of Integrated Science learning tools focused on ecoliteracy for fourth-grade elementary school students. Using the Research and Development (RnD) method with the Rowntree model, the development process progressed through three stages: planning, development, and evaluation. The research was conducted at FIP UMJ Lab School with 19 students and one teacher as subjects. Data were collected using validation sheets, questionnaires, and pre-test/post-test instruments. The results demonstrate high validity across all aspects: language (98%), media (94%), and material (88%), categorizing the tools as